Changing Trends in Mental Health Care and Research in Ghana - Ofori-Atta, Angela; Ohene, Sammy (Book collections on Project MUSE., 2014)
This Reader is about the changing trends in mental health care and research in Ghana. The book includes a brief history of the department and Mental Health Care in Ghana through the eyes of professionals who have lived this history. There is also a revised situation analysis of mental health services and legislation from 2005. These are followed by three main sections on Conceptualization of Mental Illness (depression, religion and illness, autism, substance use disorders and schizophrenia), Mental Health Practice in a teaching hospital setting (referrals to Korle-Bu, how psychiatric illnesses.